Reading corruption in Peru from the Peruvian Traditions of Ricardo Palma - Fernández Pérez, Cleiner César (2024)
In this article the critical richness of Ricardo Palma’s work Tradiciones Peruanas is approached in a deep and reflexive way. During the development, the imperfections in the Peruvian judicial system in its multi-generational development were investigated by means of a parallelism. In stories such as La Camisa de Margarita, El Alacran de Fray Gómez and Don Dimas de la Tijereta, Palma describes the corruption, injustice and abuse celebrated in his time; however, many of these competitive concepts are found in our current reality, as happened in a case that shook our judicial and political spectrum, “The White Collars of the Port”. This article not only acutely addressed the exposure of the unequal and corrupt judicial system, but also called attention to the question of what is the utility of the system we currently have.